THE IMPLEMENTATION OF EFFECTIVENESS LECTURERS’ KNOWLEDGE IN CLASSROOM LEARNING - Maharani Sukma, Meita; Fatmawati, Fatmawati; Rochmawati, Laila; Putra, Iwansyah; Dewi Kusumayati, Lusiana (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The Implementation of Effectiveness lecturers knowledge is important in classroom learning, the goal of this research was to examine how lecturers’ knowledge was used to English language instruction in the classroom. Knowing how the practices and the expertise of the presenters related to one another was also important. Using a qualitative case study approach, this study was created. A checklist for observation and an interview were used to collect the data. Eight English lecturers served as the main subjects, with their cadets serving as auxiliary topics. The interactive model proposed by Miles and Huberman was used to examine the results. The statistics showed that the participants’ understanding of the classroom varied; one had sufficient knowledge, another demonstrated an average performance, and the other two were developing. Two lecturers demonstrated great classroom management during their practice sessions, whereas the other two put forth just mediocre effort. There were three groups of lecturers for the correspondence, with the first group having sufficient knowledge and applying it simultaneously, the second having average knowledge but applying it more skillfully, and the third having emerging knowledge and applying it in a way that is likely to be consistent with their knowledge in the classroom